CONTRIBUTION OF CAST STRUCTURE TO THE LEVEL OF HARDENING OF THE TOOL STEEL FOR HOT FORMING, RECEIVED AT INDUCTION MELTING - V. N. Fedulov (Литьë и металлургия)
The matters of influence of cast structure on level of hardening of tool steel of type 4X2BMC with various proportions of elements in their structure are considered. It is shown that presence of cast structure can provide hardness increase up to 5-15% of the experience value that is especially necessary at tempering temperatures of 600 ° C and over.